Climate change, migration and health systems resilience: Need for interdisciplinary research - Ridde, Valéry; Benmarhnia, Tarik; Bonnet, Emmanuel; Bottger, Carol; Cloos, Patrick; Dagenais, Christian; De Allegri, Manuela; Nebot, Ariadna; Queuille, Ludovic; Sarker, Malabika (F1000 Research, 2022)
This article was published in the F1000 Research [ © 2019 Ridde V et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited. ] and the definite version is available at: https://doi.org/10.12688/f1000research.17559.2 The Journal's website is at: https://f1000research.com/articles/8-22/v2